COVID-19 and Its Impact on Diverse Aspects of Women's Lives. (June 2023) - Lawrence, Alfred J.; Fatima, Umama; Ali, Faiza; Abraham, Ancey; Arif, Saima; Khan, Tahmeena
The objective of this article is to study the impact of COVID-19 on the lives of women by exploring different aspects like their daily work patterns, hygiene practices, psychological effects and nutritional status during the pandemic. 510 women participated in the online survey. The majority of the respondents belonged to the age group of 20–29 years and were either graduates or above. 37.3% of the working respondents reported increased professional responsibilities during the pandemic. Cooking and cleaning occupied most of the time during the lockdown. Anxiety, lack of concentration and frequent arguments with the family members were reported by the respondents. Many of the respondents took up physical activities to maintain their fitness. They also believed that usage of masks would prevent them from catching the infection. 75.2% of women included vitamin-rich sources in their diet. This level of consciousness might be linked to the educational profile of the respondents.